Contributions of HA1 and HA2 Subunits of Highly Pathogenic Avian Influenza Virus in Induction of Neutralizing Antibodies and Protection in Chickens - Shirvani, Edris; Paldurai, Anandan; Varghese, Berin P.; Samal, Siba K. (Frontiers in Microbiology, 2020)
Highly pathogenic avian influenza virus (HPAIV) subtype H5N1 causes a devastating disease in poultry. Vaccination is an effective method of controlling avian influenza virus infection in poultry. The hemagglutinin (HA) protein is the major determinant recognized by the immune system of the host. Cleavage of the HA precursor HA0 into HA1 and HA2 subunits is required for infectivity of the avian influenza virus. We evaluated the individual contributions of HA1 and HA2 subunits to the induction of HPAIV serum neutralizing antibodies and protective immunity in chickens. Using reverse genetics, recombinant Newcastle disease viruses (rNDVs) were generated, each expressing HA1, HA2, or HA protein of H5N1 HPAIV. Chickens were immunized with rNDVs expressing HA1, HA2, or HA. Immunization with HA induced high titers of serum neutralizing antibodies and prevented death following challenge. Immunization with HA1 or HA2 alone neither induced serum neutralizing antibodies nor prevented from death following challenge. Our results suggest that interaction of HA1 and HA2 subunits is necessary for display of epitopes involved in the induction of neutralizing antibodies and protection on intact HA molecule. These epitopes are lost when the two subunits are separated. Therefore, vaccination with either HA1 or HA2 may not provide protection against HPAIV.